Comparative and legal characteristics of the norms of positive law in the field of the national security of Ukraine, USA and Federal Republic of Germany - Zagumenna, Yu. O.; Загуменна, Ю. О.; Юлія Загуменна (Legal Science and Praxis. - 2021. - № 2. - P. 43-48, 2021)
Досліджено вітчизняний та міжнародний досвід нормативно-правового регулювання забезпечення національної безпеки. Проаналізовано нормативно-правові документи України, США та Німеччини (конституції, законодавчі акти, концепції, доктрини, стратегії та повідомлення), що регулюють питання у зазначеній сфері; оцінено ситуацію для подальшого покращення правового механізму забезпечення національної безпеки. Зазначено, що існує необхідність вдосконалення нормативно-правової бази на реалізацію державної політики у сфері забезпечення національної безпеки України.

The author of the article studies domestic and international experience of normative and legal regulation for ensuring national security. The author has accomplished a systematic and comprehensive study of regulatory legal documents of Ukraine, the United States of America and Germany (constitutions, legislative acts, concepts, doctrines, strategies and messages) regulating the issues in the specified area; has assessed this situation for further improvement of the legal mechanism for ensuring national security. It is noted that there is the need to improve the regulatory legal base for implementing the state policy in the field of ensuring national security of Ukraine. The purpose of the research is to solve the indicated scientific problem by conducting a systematic and comprehensive study of regulatory legal documents regulating the issues of ensuring national security taking into account general theoretical positions, as well as to assess this situation for further improvement of the legal mechanism for ensuring national security of Ukraine. The research is based on a wide range of general scientific and special legal methods of cognition. General scientific methods are represented by: methods of empirical research (comparison, description); methods of theoretical study (formalization, axiomatic method); logical methods (analysis, generalization, analogy). Special legal methods include comparative and legal, formal and legal, the method of interpretation of law norms. General scientific methods are mainly used in theoretical substantiation of the problem, while considering the issues of understanding the phenomenon of national security, the regulatory base for its provision, determining their role in the legal system of the studied states. The comparative and legal method was used to identify the peculiarities of domestic and foreign normative and legal regulation of national security issues. The formal and legal method served as the basis for the analysis of the current regulatory legal acts in this area. The method of interpretation of legal norms assisted to clarify the content of the provisions of legal documents regulating the national security issues. The current situation of Ukraine in the field of ensuring national security is due to the nature of socio-political and economic development of the state, as well as to tendencies in developing challenges, dangers and threats that require adequate measures of legal regulation of these changes. To this end, the Ukrainian authorities need to improve the legal base for the implementation of the state policy in the field of ensuring national security. Analysis of regulatory legal documents of Ukraine, the United States and Germany regulating the national security issues, allowed us to conclude that the national interests of a particular state are the basis for ensuring national security even if there are external differences in constitutions, laws, concepts, doctrines, strategies and messages, as well as in legislation in the field of national security. In this regard, certain contradictions in the understanding of the doctrinal national interests of Ukraine, the United States, Germany and other states are still inevitable.

Исследован отечественный и международный опыт нормативно-правового регулирования обеспечения национальной безопасности. Проанализированы нормативно-правовые документы Украины, США и Германии (конституции, законодательные акты, концепции, доктрины, стратегии и сообщения), регулирующие вопросы в данной сфере; оценена ситуация для дальнейшего улучшения правового механизма обеспечения национальной безопасности. Отмечено, что существует необходимость усовершенствования нормативно-правовой базы на реализацию государственной политики в сфере обеспечения национальной безопасности Украины.
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; зарубіжний досвід; foreign experience; зарубежный опыт; національна безпека; national security; национальная безопасность; нормативно-правове регулювання; normative and legal regulation; нормативно-правовое регулирование; Стратегія національної безпеки; National security strategy; Стратегия национальной безопасности; державна політика; state policy; государственная политика